FishLink: Bridging Consumers Direct to Fishermen’s Catch - Janepol Gumahin Ballard; James Deen O De Belen; Brainard M Delola; Russel Vincent M Deloloa; Ardelin R Calunsag; Marlon M Bajolo (Universitas Multi Data Palembang, 2026)
This research presents FishLink, an online platform that connects small scale fishers directly with consumers, addressing income losses caused by intermediaries and access restrictions. The platform was developed using a developmental research approach, with iterations informed by feedback from a coastal municipality. Usability, efficiency, reliability, and overall effectiveness among fishers and consumers were the major areas of evaluation. The findings indicated high user satisfaction and increased digital direct transactions, which led to faster selling times and better price transparency. FishLink promotes sustainable livelihoods by supporting local fisheries and encouraging responsible market participation. The study aligns with the aims of poverty alleviation, decent work promotion, technological innovation, and sustainable aquatic resource management. It is also recommended in future work to extend the platform’s geographic coverage and improve its transaction features to reach the fishing community in more rural fishing villages.